Determinan Perilaku Penggunaan Aplikasi BYOND by BSI: Peran Literasi Keuangan Digital, Kegunaan, dan Persepsi Biaya - Zulkarnain, Rizky; Amri, Andi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
Digital transformation in the Sharia banking industry currently requires actual technology adoption by customers to maintain organizational competitiveness. This study aims to analyze the determinants of actual usage behavior regarding the BYOND by BSI application by integrating cognitive and economic factors within the Mobile Technology Acceptance Model (MTAM) framework. Utilizing a quantitative approach, data were gathered from 100 respondents in the Jabodetabek area through purposive sampling techniques. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Mobile Usefulness significantly influences Behavior Intention. Furthermore, Behavior Intention acts as a full mediator in the relationship between perceived usefulness and actual usage behavior. Within the urban Jabodetabek sample, Digital Financial Literacy does not exert a significant impact on application adoption. Conversely, Mobile Perceived Cost shows a significant direct effect on Use Behavior. These results offer implications for Sharia banking management regarding the importance of utility value and cost transparency in maintaining customer retention within the digital ecosystem.